2017
DOI: 10.1002/jor.23588
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage surface roughness as an imaging‐based morphological indicator of osteoarthritis: A preliminary investigation of osteoarthritis initiative subjects

Abstract: Current imaging-based morphometric indicators of osteoarthritis (OA) using whole-compartment mean cartilage thickness (MCT) and volume changes can be insensitive to mild degenerative changes of articular cartilage (AC) due to areas of adjacent thickening and thinning. The purpose of this preliminary study was to evaluate cartilage thickness-based surface roughness as a morphometric indicator of OA. 3D magnetic resonance imaging (MRI) datasets were collected from osteoarthritis initiative (OAI) subjects with Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The lower femoral contact angles and deviation angles in the individuals with obesity compared with the nonobese group suggest that the loads were transmitted through a relatively anterior and central portion of the femoral cartilage. We also found a significant difference in the femoral deviation angle excursions, suggesting the distribution of femoral contact and deviation angles during the stance phase of the gait cycle exhibited the altered loading condition of cartilage that may accelerate OA development 25 …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The lower femoral contact angles and deviation angles in the individuals with obesity compared with the nonobese group suggest that the loads were transmitted through a relatively anterior and central portion of the femoral cartilage. We also found a significant difference in the femoral deviation angle excursions, suggesting the distribution of femoral contact and deviation angles during the stance phase of the gait cycle exhibited the altered loading condition of cartilage that may accelerate OA development 25 …”
Section: Discussionmentioning
confidence: 68%
“…We also found a significant difference in the femoral deviation angle excursions, suggesting the distribution of femoral contact and deviation angles during the stance phase of the gait cycle exhibited the altered loading condition of cartilage that may accelerate OA development. 25 Our contact analyses suggest that obesity affects the contact locations mostly in the medial tibiofemoral compartment, where the medial contact locations shifted medially in the individuals with obesity (Figure 6). The altered cartilage contact location may indicate a predominance of medial disease in obese persons compared with nonobese counterparts.…”
Section: F I G U R E 3 Femoral Cartilage Contact Locations On the Med...mentioning
confidence: 73%
“… 31 , 32 Surface roughness metrics were found to be sensitive to degenerative morphologic changes, and may be useful in osteoarthritis characterization and early diagnosis. 33 Seitz et al 34 reported that the medial compartment of the knee was much more affected by degenerative changes than the lateral compartment and suggested that the menisci were potentially degenerative earlier than the adjacent articular cartilage. We are able to measure stiffness, surface roughness, and thickness of human living articular cartilage using our system, and these three parameters were distinguishable between normal cartilage and degenerative stages per the ICRS cartilage classification.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, magnetic resonance imaging (MRI) and computed tomography (CT) have provided three-dimensional (3D) imaging to assess cartilage surface characteristics, such as roughness, which is a marker of early OA. 5,6 However, due to the partial volume artifact in MRI and CT, it is difficult to extract cartilage profiles perfectly. Arthroscopic methods rely on direct visual inspection without invading the joint surface, but they are subjective evaluations by scoring systems such as the International Cartilage Repair Society (ICRS) system, 7 and they lack objectivity and do not provide stereoscopic information to the surgeon.…”
Section: Introductionmentioning
confidence: 99%